How to Evaluate and Manipulate Charge Transfer and Photocatalytic Response at Hybrid Nanocarbon–Metal Oxide Interfaces. (15th December 2017) - Kemnade, Nina; Gebhardt, Paul; Haselmann, Greta M.; Cherevan, Alexey; Wilde, Gerhard; Eder, Dominik
Abstract: Nanocarbon–metal oxide hybrids are among the most promising functional materials in many cutting‐edge environmental and energy applications where efficient charge separation and extraction are keys to success. The next level of hybrid structures will be achieved once one learns how to control and tune charge/energy transfer processes at the interfaces. However, little is yet known about the nature and extent of these interfacial dynamics in nanocarbon hybrids. Here a model is designed in which ultrathin dielectric layers (Al2 O3, ZrO2 ) between the hybrid's components (ZnO, TiO2 ) and carbon nanotubes allow for evaluating and tuning of interfacial charge transfer over an unusually long distance of at least 50 nm. Surprisingly, the transfer efficiency correlates linearly with the barrier layer thickness, indicating that electron conduction through the barrier layer constitutes the rate‐limiting step. It is also demonstrated that the charge transfer efficiency can be tuned by the type of interlayer and its degree of crystallinity, thus controlling the hybrid's performance in the photocatalytic production of hydrogen. It is believed that this model system will help to understand and decipher the fundamentals regarding interfacial charge and energy transfer in nanocarbon hybrids with the aim to further advance these hybrid structures for a wide range of energy applications. Abstract : A novel hybrid system enables monitoring and tuning of interfacial charge transfer and manipulation of photocatalytic properties in nanocarbon–inorganic hybrids through implementation of ultrathin dielectric barrier layers using atomic layer deposition. Distance‐dependent quenching studies with solid‐state photoluminescence reveal electron conduction through the barrier layer as the rate‐limiting step.